Oxygen incorporation in AlN films grown by plasma-enhanced atomic layer deposition - ALEVLİ, MUSTAFA (My University, 2022)
Oxygen is often detected as an impurity in III-nitride films deposited by atomic layer deposition (ALD). The presence of oxygen has deep and unfavorable influences on the structural and optical properties of AlN. We have studied the oxygen incorporation in AlN films prepared by hollow cathode plasma-assisted ALD by alternating H-2 plasma. We report a decrease in the O concentration in the film upon the addition of H-2 plasma flow. However, increasing the H-2 plasma flow does not further decrease the O incorporation. Film composition became almost constant at the surface and beneath the surface of AlN films deposited using N-2/H-2 plasma. Only samples grown with N-2/H-2 plasma showed decreases in oxygen concentration from the surface to the bulk film. Oxygen produces important modifications in the structural, chemical, and electrical properties. The Al 2p, N 1s, and O 1s high-resolution x-ray photoelectron spectra represent that AlN films are composed of Al-N, Al-O, and N-Al-O bonds. X-ray photoelectron spectroscopy data suggest that the composition of the AlN film changes to AlON + AlN when N-2 plasma is used. The valence band maximum position of the AlN film is found to be at & SIM;1.7 eV for oxygen atomic concentration & SIM;20 at. %. The TO and LO phonon modes are present in AlN films with oxygen contamination & SIM;20 at. % and disappear at high oxygen contamination (& SIM;55 at. %).
Keywords: Fizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Natural Sciences; Engineering and Technology; MALZEME BİLİMİ, KAPLAMALAR VE FİLMLER; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); FİZİK, UYGULAMALI; Temel Bilimler (SCI); MATERIALS SCIENCE, COATINGS & FILMS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); PHYSICS, APPLIED; PHYSICS; Natural Sciences (SCI); Statistical and Nonlinear Physics; General Materials Science; Physical Sciences